No association of ALOX5AP polymorphisms with risk of MRI-defined brain infarcts - Barral, S (2011)
The arachidonate 5-lipoxygenase-activating protein (ALOX5AP) gene has been associated with stroke. The majority of the reported ALOX5AP associations have considered non-radiologically confirmed infarcts as the stroke phenotype. We assessed the association of genetic variants in ALOX5AP with stroke defined by the presence infarcts on brain Magnetic Resonance Imaging (MRI). We studied 202 persons with MRI-defined brain infarcts cases and 487 healthy individuals of Caribbean Hispanic ancestry. Another sample of European ancestry comprised of 1,823 persons with MRI-defined brain infarct and 7,578 controls. Subjects were genotyped for the four SNPs that define ALOX5AP HapA haplotype. No association was found between SNPs and MRI-defined brain infarcts. Our data do not support the hypothesis that variants in ALOX5AP are associated with risk of MRI-defined brain infarcts.